Are we what we eat or what we worship? Food activism and fanaticism in Margaret Atwood’s The Year of the Flood (Altre Modernità, 2024)
Atwood’s MaddAddam trilogy mirrors the author’s commitment in the environmental debate, articulating, through the topos of the apocalypse, future scenarios due to modern-day generational environmental amnesia. This study focuses on the God’s Gardeners, the eco-religious group of The Year of the Flood (2009), the second volume of the trilogy. More specifically, the core of the analysis is the vegetarian philosophy embraced by this activist faction, led by the charismatic figure of Adam One. Within the framework of literary food studies, the analysis begins by examining the implications of various dichotomies encompassing concepts such as cannibalism/anthropophagy versus vegetarianism, binge eating in contrast to fasting, as well as the interplay of waste and stockpiling. Subsequently, the essay aims to build upon prior scholarly investigations into the Gardeners' ethos, which have brought to light contradictions within their philosophy of life. By contextualizing the activism of God's Gardeners within the broader discourse on food justice and sustainability, this analysis seeks to reassess the group's core beliefs and internal inconsistencies. This endeavour involves a partial reconstruction of the viability and practicality inherent in the Gardeners’ form of food activism.
Keywords: Margaret Atwood; The Year of the Flood; food activism; food justice; vegetarianism; Flexitarianism